Keterwakilan Perempuan Pada Dewan Pimpinan Daerah Partai Demokrasi Indonesia Perjuangan Provinsi Sumatera Selatan - Khoza, Rinda Fitriani; Ropik, Ainur; Darmawan, Erik (Jurnal Studi Ilmu Politik, 2024)
This study discusses women's representation in the regional leadership council of the Indonesian Democratic Party of Struggle for South Sumatra Province, which will focus on women's management in the regional leadership council of the Indonesian Democratic Party of Struggle for South Sumatra Province. Therefore, this study aims to find out how the role and process in women's representation in the management of the regional leadership council of the Indonesian democratic party of struggle for South Sumatra province. This research uses a descriptive method with a qualitative approach. Meanwhile, data collection techniques are carried out by interview and documentation methods. The primary data sources are six cadres of South Sumatra DPD PDIP . Secondary data sources are books, journals and related documents. In analyzing this research using the theory of the function of political parties. The results of this study show that the role of women administrators in South Sumatra DPD PDIP is carried out well and has the support of South Sumatra DPD PDIP and in the process of recruitment of administrators carried out with the stages of filling out the form, submitting the vision and mission, selection, determining women administrators, ratifying party management. The 30% female representation in the South Sumatra PDIP DPD has fulfilled the 30% requirement in not only the legislature but also in the management of women and female cadres of the South Sumatra PDIP DPD.